Rocky start: medical missionary in the later Yi Dynasty of Korean Peninsula - SHU, Jian (Journal of Research for Christianity in China (JRCC), 2014)
In the late Yi Dynasty Korean Protestantism missionary to enter the Korean peninsula, in order to expand the missionary Christianity has taken many forms. This paper examines the Protestantism medical missionary work began in the Korean peninsula. First, the first missionaries to enter the Korean Peninsula has not actively choose to preach, but through contacts with the upper gain trust, then start spreading the medical missionary work, and history also provides opportunities for the missionaries, a coup, a war for the medical missionary provided the stage. After deploying the medical missionary, a large influx of American medical missionary, where female medical missionary in the medical missionary work has played a huge role, very good men and women to break the barriers of Oriental society boundaries. But in the course of missionary work, these missionaries are from a different country has paid a heavy price, and some even put their short life. These arduous pay, earned the trust of the Korean people, and finally as a Christian missionary in the modern successfully called the situation in modern Korea.
Keywords: Protestantism medical missionary Korea